Fabrication of Graphene Oxide and Nanohydroxyapatite Reinforced Gelatin–Alginate Nanocomposite Scaffold for Bone Tissue Regeneration - Purohit, Shiv Dutt; Singh, Hemant; Bhaskar, Rakesh; Yadav, Indu; Bhushan, Sakchi; Gupta, Mukesh Kumar; Kumar, Anuj; Mishra, Narayan Chandra (Frontiers in Materials, 2020)
Graphene oxide (GO) and nanohydroxyapatite (nHAp) proved to be a potential material for bone tissue-regeneration applications. Therefore, GO and nHAp reinforced porous polymeric nanocomposite scaffolds have been gaining significant research thrust. In this study, GO and nHAp based nanocomposite was synthesized and used as a reinforcing agent to develop gelatin-alginate (GA)-based three-dimensional porous polymeric nanocomposite scaffold. The polymeric nanocomposite scaffold (nHAp-GO/GA) was fabricated by using freeze-drying process, which may show a synergistic effect of each of the components for tissue regeneration. The scaffold demonstrates good physico-chemical properties. The porous microstructure of the scaffold is evidenced by Field emission scanning electron microscopy (FESEM). High swelling of the scaffold in presence water, indicates that the scaffold is highly hydrophilic, which implies the suitability of the scaffold for tissue regeneration. Further, the incorporation of nHAp-GO enhances the compressive strength of the scaffold while reduces the rate of biodegradation, which is good for bone tissue engineering. The scaffold is biocompatible. In vitro cell study with MG-63 bone cells demonstrates the synergistic effect of each of the components of the scaffold, on mineral deposition. Therefore, it can be concluded that nHAp-GO/GA polymeric nanocomposite scaffold can be a potential candidate for bone tissue regeneration.